1993
DOI: 10.2527/1993.7141041x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling gas production kinetics of grass silages incubated with buffered ruminal fluid1

Abstract: Time course measurements of in vitro gas production of feedstuffs incubated with buffered ruminal fluid give information about the rate at which the feed is fermented. To compare gas production kinetics from different feeds, a mathematical model was needed to describe the data. We investigated several existing models (exponential, logistic, Gompertz, Richards, Schnute), fitting them to 50 gas production curves obtained with grass silages. None of them gave a satisfactory description of the data. A new model wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 13 publications
2
50
0
7
Order By: Relevance
“…On the other hand there was no significant relationship between the estimated parameters of gas production and DM degradation of tree leaves in this experiment. This is in agreement with the findings of Beuvink & Kogutk, (1993) and Blümmel & Ørskov (1993) who showed that there was no significant correlation between rate of gas production and rate of DM disappearance. On the other hand, Sileshi et al (1996) found a significant relationship between these parameters.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand there was no significant relationship between the estimated parameters of gas production and DM degradation of tree leaves in this experiment. This is in agreement with the findings of Beuvink & Kogutk, (1993) and Blümmel & Ørskov (1993) who showed that there was no significant correlation between rate of gas production and rate of DM disappearance. On the other hand, Sileshi et al (1996) found a significant relationship between these parameters.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with findings of Sileshi et al (1996) but not with that of Blümmel & Ørskov (1993) who did not find any correlation between these parameters in barley and wheat straw. Beuvinik et al (1993) and Beuvink & Kogutk (1993) suggested that the relationship between these parameters varies with type of forage. On the other hand there was no significant relationship between the estimated parameters of gas production and DM degradation of tree leaves in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the aspect that gas production primarily originates from OM fermentation and because diets differed in their OM content, the gas production data were standardised by expression per g of OM. To describe the course of cumulative gas production, the following modified Gompertz function according to Beuvink and Kogut (1993) was fitted to the data:…”
Section: Calculationsmentioning
confidence: 99%
“…The parameters were estimated by using the software GraphPad Prism 5.01 for Windows (GraphPad Software, Inc., La Jolla, USA). The GP rate is maximal in the point of inflection (calculated from the first derivative) at which the second derivative is zero (Beuvink and Kogut, 1993;Boguhn et al, 2008). The statistical comparison of the estimated plateau value of GP was based on Horn and Erdmann (1978) using the confidence interval of this parameter.…”
Section: Digestibility and Energy Concentrationmentioning
confidence: 99%